Possibility of Interreligious Dialogue - Mitias, Michael H. (Interreligious Studies in Theory and Practice, 2021)
1. Introduction -- 2. General Framework of Analysis -- 3. Mutual Respect as a Condition of Interreligious Dialogue -- 4. Mutual Understanding as Condition and Aim of Interreligious Dialogue -- 5. Mysticism as a Basis of Interreligious Dialogue: God-Centeredness -- 6. Does Religious Self-Understanding Impede Interreligious Dialogue?.